The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.5944/ried.22.1.22079
|View full text |Cite
|
Sign up to set email alerts
|

Impacto del concepto PLE en la literatura sobre educación: la última década

Abstract: El concepto de Entorno Personal de Aprendizaje (PLE) es uno de los conceptos que ha recibido una mayor atención en los últimos años en el ámbito de la tecnología educativa. Los que estudiamos el tema asumimos —hay quien dice que de forma ingenua o acrítica— que se trata de un concepto realmente disruptivo, fundamental y que está en la base de los enfoques pedagógicos emergentes propios del momento tecno-social que nos enmarca, no solo en la faceta tecnológica-instrumental, sino también en los fundamentos mismo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
27

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 37 publications
0
6
0
27
Order By: Relevance
“…The integration of social media facilitates learning interaction and informal communication between students (Gillet 2013;Kop and Fournier 2014). Recent studies have shown that as a concept and an emerging practice, the personal learning environment is not only a technology-driven and student-centered learning innovation, but also a challenge and subversion to the concept of traditional knowledge (Castañeda et al 2019). From the perspective of application value, the personal learning environment is a paradigm that supports digital learning, enabling learners to define, develop and configure learning spaces and experiences by themselves, and provides a choice for community members to choose learning scenarios.…”
Section: Research On the Connotation Of Personal Learning Environmentmentioning
confidence: 99%
“…The integration of social media facilitates learning interaction and informal communication between students (Gillet 2013;Kop and Fournier 2014). Recent studies have shown that as a concept and an emerging practice, the personal learning environment is not only a technology-driven and student-centered learning innovation, but also a challenge and subversion to the concept of traditional knowledge (Castañeda et al 2019). From the perspective of application value, the personal learning environment is a paradigm that supports digital learning, enabling learners to define, develop and configure learning spaces and experiences by themselves, and provides a choice for community members to choose learning scenarios.…”
Section: Research On the Connotation Of Personal Learning Environmentmentioning
confidence: 99%
“…Los PLE, más allá de la perspectiva tecnodeterminista, son ecosistemas abiertos (Kühn, 2017;Panagiotidis, 2012) que conectan herramientas, servicios, estrategias, relaciones e interacciones al proceso de aprendizaje (Barroso et al, 2012;Marín et al, 2013) dentro de contextos escolarizados y no escolarizados (Dabbagh y Kitsantas, 2012;Area y Sanabria, 2014). Los PLE siguen un sustento pedagógico que integra el aprendizaje autorregulado o SRL (Self-Regulated Learning) (Perera y Gardner, 2018;Castañeda et al, 2019) y el aprendizaje social (Dabbagh y Kitsantas, 2012;Nkwenti, 2016) y que siguen un paradigma socioconstructivista, constructivista y conectivista (Elia y Poce, 2010;Torres et al, 2019).…”
Section: Marco Teórico 21 Los Entornos Personales De Aprendizaje Y Eunclassified
“…En una reciente revisión sistematizada de literatura sobre educación se observa que el concepto PLE está estrechamente ligado al del aprendizaje autorregulado (Castañeda et al, 2019). El estudio observa que el concepto de aprendizaje autorregulado en los PLE en muchos casos se asocia con la social media, que permiten la propiedad y control por parte de la persona que aprende.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…En este sentido, destaca la propuesta de Castañeda y Adell, (2013) que consideran los PLE como un entramado de herramientas, mecanismos, actividades y conexiones que cada persona utiliza para aprender. Igualmente, los PLE quedan caracterizados por la flexibilidad de incorporar aquellos recursos que más se adapten a las circunstancias de aprendizaje del usuario (Castañeda, Tur y Torres-Kompen, 2019). En este sentido, cabe destacar también que el análisis de los PLE se propone una estructura basada en tres componentes: buscar información, crear contenido y compartir información (Castañeda y Adell, 2013).…”
Section: Introductionunclassified